Risk Analysis by FMEA Method in Hotel - Dağ, Mustafa; Yalçın, Zehra Gülten; Oz, Ali; Aydoğmuş, Ercan (Niyazi BULUT, 2018)
In thiswork a risk analysis was carried out by FMEA methodat a hotel management. The necessary precautions have been taken by protecting the safety of the managment with the FMEA method. During in this period workflow diagram was done. According to this workflow diagram potential failure, effect, cause and  precaution was determined. According to this, in hotel managemet; hazardssuch as glare, fire, explosion, fallin a boilerroom, electricshock in a electricalcontrolroom, slip, drop, fire  in a pool boiler room, rheumatism, respiratory tract infection in a fitnessroom, drowning in a baths, fire in power distribution unit was determined. Hazards that exist in different units have been determined and risk has been tried to be destroyed or reduced. For this precaution of hazards need to be done; using  of materials comply with the regulations and fragile materials convenient stored, storing chemicals in special storage which will cause glare and explosion, use of fasteners in materials to avoid falling and slipping, smoke and flame detector for fire, providing staff health and safety training , maintenance and repair of the devices must be performed at certain periods. After the implementation of these measures, the results were analyzed by this method and the situation evaluation was carried out. As a result of using the FMEA method, it has been observed that risks are reduced in the risk study. As a result, initially the highest risk values were reduced to the acceptable risk value with the necessary improvement recommendations and the implementation of these recommendations.